Headache in the Pediatric Emergency Service: A Medical Center Experience - Hsiang-Ju Hsiao; Jing-Long Huang; Shao-Hsuan Hsia; Jainn-Jim Lin; I-Anne Huang; Chang-Teng Wu (Elsevier, 2014)
Headache is a common complaint in children and is one of the most common reasons for presentation at a pediatric emergency department (PED). This study described the etiologies of patients with headache seen in the PED and determined predictors of intracranial pathology (ICP) requiring urgent intervention. A secondary objective was to develop rapid, practical tools for screening headache in the PED. Methods: We conducted a retrospective chart review of children who presented with a chief complaint of headache at the PED during 2008. First, we identified possible red flags in the patients' history or physical examination and neurological examination findings. Then, we recorded the brain computed tomography results. Results: During the study period, 43,913 visits were made to the PED; in 409 (0.9%) patients, the chief complaint was headache. Acute viral, respiratory, and febrile illnesses comprised the most frequent cause of headache (59.9%). Six children (1.5%) had life-threatening ICP findings. In comparison with the group without ICP, the group with ICP had a significantly higher percentage of blurred vision (p = 0.008) and ataxia (p = 0.002). Conclusion: Blurred vision and ataxia are the best clinical parameters to predict ICP findings.